L'esperienza artistica nella scuola italiana - Rossella Certini (Firenze University Press, 2015)
The man's history speaks an artistic language and the man's evolution can be narrated by the artworks created by human's imagination. The school should rethink about the role of art into educational path of the youth, considering it as a cross instrument for learning and activating a play that alternates to action of creating with the activity of understanding.